2005
DOI: 10.1542/peds.2004-0266
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residency Education: Is Sports Medicine Getting Its Fair Share?

Abstract: SM education is deficient in US pediatric residency programs. Standardized curricula should be developed with a focus on hands-on training as a means for teaching SM to pediatric residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
1
28
0
1
Order By: Relevance
“…This study involved pediatric residency programs in the United States and concluded that sports medicine education, including the teaching of concussion management, was deficient. 7 It has been suggested that the medical school curriculum should be an important source of concussion education. 8 No studies have evaluated the amount and type of concussion teaching in North American medical schools.…”
Section: Original Articlementioning
confidence: 99%
“…This study involved pediatric residency programs in the United States and concluded that sports medicine education, including the teaching of concussion management, was deficient. 7 It has been suggested that the medical school curriculum should be an important source of concussion education. 8 No studies have evaluated the amount and type of concussion teaching in North American medical schools.…”
Section: Original Articlementioning
confidence: 99%
“…In this regard, practitioner surveys have consistently identified areas of residency training judged in retrospect to have been inadequate. [10][11][12][13][14] We surveyed generalists and subspecialists within the first 5 years of practice and found that 91% of generalists and 84% of subspecialists would have configured their residency differently if given the opportunity with 6 to 12 months of flexible time. 15,16 It is possible, however, that during residency many residents prefer a set, structured curriculum to one in which they have greater responsibility for choosing educational experiences.…”
mentioning
confidence: 99%
“…5 Even as this problem increases, there are concerns that pediatric residents are receiving minimal education in the field of sports medicine during both medical school and residency. 6 Although the focus of pediatric sports medicine is typically proper training and managing common injuries, an emerging issue is learning about the drugs that are chosen by young athletes to improve athletic performance. This article is intended to educate pediatricians, the most common medical contact for young athletes, about several drugs that commonly are used, with particular attention to their physiology, effects, adverse effects, legal and sporting implications, and the incidence of each drug's use.…”
mentioning
confidence: 99%